What Drives Local Food Prices? Evidence from the Tanzanian Maize Market - Baffes, John; Kshirsagar, Varun; Mitchell, Donald (Published by Oxford University Press on behalf of the World Bank, 2020)
We examine the drivers of monthly changes in maize prices across 18 Tanzanian markets. Local prices respond three to four times faster to the main regional market (Nairobi) than to the international benchmark (US Gulf). More importantly, shocks from Nairobi account for only one third of the explained variation in domestic prices; the remaining two-thirds is accounted for by domestic influences (including harvest cycles, weather shocks, and trade policies). Further, we show that remoteness and the local agroecology systematically influence the behavior of food prices.